Memória e reminiscência histórica: a composição das personagens em Comissão das Lágrimas, de António Lobo Antunes - Silveira, Laura Severo da (2024)
In this dissertation, we investigate the composition of characters in "Comissão das Lágrimas" (2011) by António Lobo Antunes. Initially, we conduct a critical review of the reception of the work and the author. Next, in the second chapter, we establish parallels between historical events portrayed in the work and recent episodes in the history of Angola, consulting sources such as newspapers, official documents, correspondents' reports, and pamphlets disseminated during the 1970s. We also explore the complex interactions between history, memory, and literature. In the third chapter, we focus on analyzing the composition of the three main characters, examining the mechanisms of their figurations. We demonstrate how the interaction of different world perspectives, both shared and individual, of the characters allows the reader to infer the ideological meanings present in the work. Additionally, we analyze the themes of racism, violence, death, and old age present in the narrative, highlighting how these elements contribute to the complexity and depth of the text. Finally, by contextualizing the relationships between the characters and the historical and cultural environment of the novel, we suggest a correlation between the identity crises faced by the characters and the gradual dissolution of the colonial order, along with its representations in the Portuguese collective imagination. Through this analysis, we seek to understand not only the work itself but also to reflect on the complex dynamics that permeate the relationships between literature, memory, and reminiscences.